Detection, quantification and derivation of number size distribution of silver nanoparticles in antimicrobial consumer products1. Issue 6 (27th June 2015) - Cascio, Claudia; Geiss, Otmar; Franchini, Fabio; Ojea-Jimenez, Isaac; Rossi, François; Gilliland, Douglas; Calzolai, Luigi
<x xml:space="preserve">Abstract</x> AF4-ICP-MS for determination of size distribution of silver nanoparticles.